The Ethnolinguistic Identity of the Hamap People in Change - Ninuk Kleden Probonegoro (Journal of Indonesian Social Sciences and Humanities, 2008)
This research was conducted after the law (No. 22/1999) on regional government had been in force for more than five years, where one of the central issues in the regional autonomy era is identity. Alor, a regency in East Nusa Tenggara Province with its 16 000 islands, is a region that is conscious of its identity; it is distinct from Timor, as well as from other regions in West Nusa Tenggara and from other areas in Indonesia. Nevertheless the question remains whether Alor is able to sustain its cultural identity in an area that is inhabited by a range of ethnic groups speaking 18 different local languages (SIL International 2001). One of the ethnic groups in Alor is the Hamap people. The Hamap live in southwest Alor, in Moru village to be specific, and they are surrounded by other ethnic groups; the Abui, the Klon, the Mor, the Adang, the Kabola and the Pura people. The Kui people are considered to be of foreign origin. This belief is legitimised by a mythological kinship between the Hamap and other ethnic groups. There are also other groups: migrants from Flores, Timor and Java.